Multicultural education & perceptions of racial inequity among White Americans: a cohort analysis - Sims, Shelby, author; Roberts, Tony, advisor; Hastings, Orestes P., committee member; Sbicca, Joshua, committee member; Schmidt, Jenne, committee member (Colorado State University. Libraries, 2022)
Growing concern over racial injustice in the United States has warranted an investigation into the perceptions of racial inequality among White Americans. The phasal introduction of multicultural education (ME) in the United States has continually increased the exposure of newer cohorts of White Americans to diverse cultures and perspectives of social reality experienced by racial minorities. However, prior studies have neglected to empirically evaluate whether ME improved perceptions of racial inequity among White Americans. Using the General Social Survey (1972-2018), the present study uncovers patterns of changes in perceptions of racial inequity among White Americans. Specifically, I utilize an inter-cohort approach to illuminate patterns of association between ME cohort, educational attainment, and regionality. I conduct a thorough evaluation of the age-period-cohort dilemma in relation to racial attitudes and determine a year fixed-effects model the most empirically consistent model with the data. The multivariate analysis confirms that perceptions of racial inequity have in fact progressed with the implementation of ME. In addition, the results confirmed that more progressive racial perceptions are associated with increased educational attainment and less progressive racial perceptions are associated with Southern adolescence. Neither of these effects is contingent on ME exposure and both operate independently of educational content. The implications of these findings and subsequent recommendations for continued research on ME and White racial perceptions to continue striving for racial equity through public education.